Association between parental factors and child's behaviors during moderate sedation in pediatric dental care - Alanbari, Mohamad A.; Hamdan, Hebah M.; Bawazir, Omar A.; Sulimany, Ayman M. (Frontiers in Pediatrics, 2024)
Abstract Background/Aim: Managing young children with negative behaviors can be challenging in dental settings. Moderate sedation (MS) is often used as a treatment option for such children. However, children’s behavior during MS may vary depending on several variables. These variables include parental factors, such as parental anxiety, coping strategies, and pain catastrophizing. However, this area, particularly in Saudi Arabia, remains underexplored. Therefore, this study aimed to assess the association among parental anxiety, coping style, pain catastrophizing, and children’s behavior during MS among Saudi children. Methods: Based on sample size calculation, this cross-sectional observational study included 85 children aged 3–5 years undergoing dental treatment under MS at King Saud University, Riyadh, Saudi Arabia. Parental anxiety, coping styles, and pain catastrophizing were assessed using the Modified Dental Anxiety Scale, Brief Coping Orientation to Problems Experienced Scale, and Pain Catastrophizing Scale. Child behavior was evaluated using the Houpt scale during sedation visits, which was video-recorded and independently analyzed by a single evaluator. Data were analyzed using Pearson’s chi-squared test, Mann–Whitney U test, and stepwise multivariate logistic regression analyses. Results: The results showed no significant association among parental dental anxiety, pain catastrophizing, and child behaviors during MS. Specific parental coping strategies, such as acceptance, were positively associated with positive sedation outcomes (P=0.03), while active coping strategies were linked to less favorable outcomes (P=0.03). Female children had higher sedation failure rates (P=0.02), and the number of dental treatments was positively associated with success rates (P=0.03). Conclusion: Parental anxiety and pain catastrophizing did not significantly affect the success of sedation. However, acceptance as a coping strategy was significantly associated with sedation success in pediatric dental care under MS, whereas active coping strategies were associated with less favorable outcomes.